Scars 2019
DOI: 10.5772/intechopen.85411
|View full text |Cite
|
Sign up to set email alerts
|

Scarring After Burn Injury

Abstract: Burn injury is a trauma that has variable scarring outcomes dependent on both the size and the depth of the burn. This chapter will discuss the pathophysiology of wound healing by both primary and secondary intention and its applicability to burn wounds. The importance of accurate assessment of burn depth and its impact on the primary treatment and subsequent scar outcome will be explored. Special anatomic areas such as the face, hands and neck will be highlighted. Skin grafting and skin substitutes as treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Scarring from large burn wounds or burn wounds in functionally or cosmetically important areas (e.g., the hands, face, neck, and joints) may impart a significant burden on patients. 16 , 17 Scars can contribute to contracture in functionally or cosmetically important areas, reduced mobility, pain, itching, disfigurement, reduced quality of life, and psychological consequences (e.g., depression and anxiety). 16 , 18–21 Severe burns can also cause extensive nerve damage and peripheral neuropathy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scarring from large burn wounds or burn wounds in functionally or cosmetically important areas (e.g., the hands, face, neck, and joints) may impart a significant burden on patients. 16 , 17 Scars can contribute to contracture in functionally or cosmetically important areas, reduced mobility, pain, itching, disfigurement, reduced quality of life, and psychological consequences (e.g., depression and anxiety). 16 , 18–21 Severe burns can also cause extensive nerve damage and peripheral neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 Scars can contribute to contracture in functionally or cosmetically important areas, reduced mobility, pain, itching, disfigurement, reduced quality of life, and psychological consequences (e.g., depression and anxiety). 16 , 18–21 Severe burns can also cause extensive nerve damage and peripheral neuropathy. 22 In a systematic review, patients with burns reported the lowest scores in domains of work and heat sensitivity, bodily pain, physical role limitations, and pain/discomfort over the short term.…”
Section: Introductionmentioning
confidence: 99%